The effect of water currents on the movement behaviour of the Oriental River Prawn, Macrobrachium nipponense (De Haan, 1849) - Al maliky, Tariq Hataab Yasein (Iraqi Journal of Aquaculture, 2022)
The present study showed the effect of water currents (0.20 – 0.25 m\sec.) on the movement behaviour of Macrobrachium nipponense during 2 and 24 hour periods inclusive of weight group five (g) . In the first period, the results indicated that group one (0.10 – 0.49 g) aggregated towards the water currents or contrary currents by the relative percentage of 64.47 & 35.33 % , where as the groups were distributed in the following sequences : two , three and four 44 & 56 , 40.67 & 59.33 and 38 & 62 % , respectively . But the results of group five were 3.33 & 96.67 % . However, the results of the second period for the five groups were : 38 & 62 , 27.33 & 72.67 , 22 & 78 , 19.33 & 80.67 and 13.33 & 86.67 % , respectively . The distribution of these age-groups determined at different parts of the tank .